Unemployment and occupational mobility at the beginning of employment career in Germany and the UK - Schmelzer, Paul (Nürnberg, 2011)
"The beginning of the employment career is often associated with phases of unemployment. We argue that unemployment has different implications for different educational groups on future employment career depending on institutional settings in the UK and Germany. While search and matching models argue that an unemployment phase might be used for an active job search and might result in a better position, human capital and signalling theory predict status losses. The strongly skill-based and rigid labour market in Germany creates a stigma attached to unemployment and therefore might have negative consequences upon the re-entry into the labour market for all educational groups. The 'trial and error' strategy at the beginning of an employment career in flexible labour markets is common and therefore search and matching models should predict positive outcomes in the UK, especially for high-educated persons. Using the German Socio-Economic Panel and British Household Panel we simultaneously estimate hazard rates and changes in the occupational status."